Aldose-6-phosphate reductase from apple leaves: Importance of the quaternary structure for enzyme activity - Figueroa, Carlos Maria (2010)
Aldose-6-phosphate reductase (A6PRase) is a key enzyme for glucitol biosynthesis in plants from the Rosaceae family. To gain on molecular tools for enzymological studies, we developed an accurate system for the heterologous expression of A6PRase from apple leaves. The recombinant enzyme was expressed with a His-tag alternatively placed in the N- or C-terminus, thus allowing the one-step protein purification by immobilized metal affinity chromatography. Both, the N- and the C-term tagged enzymes exhibited similar affinity toward substrates, although the kcat of the latter enzyme was 80-fold lower than that having the His-tag in the N-term. Gel filtration chromatography showed different oligomeric structures arranged by the N- (dimer) and the C-term (monomer) tagged enzymes. These results, reinforced by homology modeling studies, point out the relevance of the C-term domain in the structure of A6PRase to conform an enzyme having optimal specific activity and the proper quaternary structure.